2015
DOI: 10.1039/c5ra10187e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of storage conditions and storage time on silver nanoparticles' physicochemical properties and implications for their biological effects

Abstract: It is increasingly recognized that nanoparticles (NPs) can 'age' while stored, and that the impact of this may lead to divergent results in terms of the observed toxicity of nominally the same NPs. The main goal of this study was to investigate whether (and to what extent) changes in silver (Ag) NPs' properties occur over time and whether storage of the dispersions under different conditions impacts their stability and ageing mechanism, as a function of the NPs' surface capping/charge. We found that both stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 55 publications
(100 reference statements)
4
92
0
Order By: Relevance
“…NM properties driving biological effects have been discussed for a long time (OECD, 2014). Expert consultation prioritized the NM dissolution, shape, reactive surface groups, surface area and size distribution as the most important key descriptors, as observed earlier (Bouwmeester et al, 2011;Izak-Nau et al, 2015). The outcome of our BN model is in line with these findings and showed that the following properties, in decreasing order of importance, were found to be the most important descriptors of the potential hazard of NMs: elemental composition, surface coating, surface area, aggregation and particle size.…”
Section: Discussionsupporting
confidence: 75%
“…NM properties driving biological effects have been discussed for a long time (OECD, 2014). Expert consultation prioritized the NM dissolution, shape, reactive surface groups, surface area and size distribution as the most important key descriptors, as observed earlier (Bouwmeester et al, 2011;Izak-Nau et al, 2015). The outcome of our BN model is in line with these findings and showed that the following properties, in decreasing order of importance, were found to be the most important descriptors of the potential hazard of NMs: elemental composition, surface coating, surface area, aggregation and particle size.…”
Section: Discussionsupporting
confidence: 75%
“…1, what confirmed the presence of AgNPs in all experimental solutions. The colour change is the result of the radiation absorption in the visible region of the electromagnetic spectrum (380 -450 nm) due to the localised surface plasmon of AgNPs [20][21][22]. UV-vis spectra on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to our results and as it was reported earlier [15,[32][33][34], broading and/or symetry loss of SPR band indicates that various shaped and/or sized nanoparticles are present. Izak-Nau et al [20] assumed that such changes in AgNPs' stability under this condition could be attributed to the elevated temperature of the dispersions exposed to daylight, which can increase the NPs collision rate and subsequently induce faster agglomeration. Additionally, daylight can cause photo-reduction of already dissolved Ag + that consequently may lead to the production of new NPs increasing the overall sample polydispersity.…”
Section: -3mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Agglomeration, precipitation, and even chemical-physical decomposition are commonly observed when aqueous suspension of nanoparticles is stored, [2][3][4]9 forcing to use only freshly prepared nanoparticles, which limits their application in the real world. 5,10,11 Taking into account that the properties of nanoparticles depend on the size, it is highly recommended to use a stabilization method able to avoid agglomeration, even for long storage time.…”
Section: Introductionmentioning
confidence: 99%